2020
DOI: 10.1016/j.enpol.2020.111866
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of energy tracking application use at the city level: Evidence from France

Abstract: This paper investigates the determinants of smart energy tracking app usage by citizens residing in French cities. Our framework is inspired by the extant strands of literature on smart cities and smart home technology adoption, but also contributing to them as smart energy applications reveal specificities that need to be incorporated; the latter include, for instance, the distinction between adoption and frequency of use, or the consideration of additional determinants such as privacy or environmental concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…There is, perhaps, one notable exception to this observation: i.e., research on the issue of privacy and security. These issues have been shown by a significant number of studies to have an impact on citizens' acceptance of the smart city concept [34,42,[47][48][49]. Tang et al [21], for example, found that many individuals have concerns about placing personal information on a government-run app [21], while Cabalquinto and Hutchins [50] showed that there is a high level of anxiety concerning the security of personal data on public Wi-Fi systems [50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There is, perhaps, one notable exception to this observation: i.e., research on the issue of privacy and security. These issues have been shown by a significant number of studies to have an impact on citizens' acceptance of the smart city concept [34,42,[47][48][49]. Tang et al [21], for example, found that many individuals have concerns about placing personal information on a government-run app [21], while Cabalquinto and Hutchins [50] showed that there is a high level of anxiety concerning the security of personal data on public Wi-Fi systems [50].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In a 2020 study conducted in Nice and Bordeaux in France [15], researchers investigated the factors influencing smart energy-tracking application usage. The study focused on app adoption and frequent use, considering determinants such as privacy concerns and environmental awareness [15]. Smart city characteristics and individual factors impact energy-tracking app adoption and usage.…”
Section: Energy Efficiencymentioning
confidence: 99%
“…The study highlights the need for more research on energy challenges and the implications of using such apps. This can help policymakers and researchers promote sustainable energy practices [15]. By switching to renewable energy sources, for instance, biomass, solar, and wind, people can lessen their CO 2 emissions.…”
Section: Energy Efficiencymentioning
confidence: 99%
“…Policy problems related to patient privacy and data security are perhaps obvious, but governments also need to address physical infrastructure, building codes, and more. Research to date on the intersection of policy, governance, and SHT is limited (Shafi & Mallinson, 2021), with policy‐oriented research focusing primarily on energy efficiency and system design (Attour et al, 2020; Lin et al, 2020; Ringel et al, 2019; Saxena et al, 2020; Wilson et al, 2017). However, SHT raises a broad range of significant policy concerns.…”
mentioning
confidence: 99%